2009
DOI: 10.1099/mic.0.023903-0
|View full text |Cite
|
Sign up to set email alerts
|

A pivotal role for the response regulator DegU in controlling multicellular behaviour

Abstract: Bacteria control multicellular behavioural responses, including biofilm formation and swarming motility, by integrating environmental cues through a complex regulatory network. Heterogeneous gene expression within an otherwise isogenic cell population that allows for differentiation of cell fate is an intriguing phenomenon that adds to the complexity of multicellular behaviour. This review focuses on recent data about how DegU, a pleiotropic response regulator, co-ordinates multicellular behaviour in Bacillus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
92
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(93 citation statements)
references
References 67 publications
0
92
0
1
Order By: Relevance
“…DegU is responsible for the expression of chemotaxis and (40,41,44,60). The data presented here suggest that the attenuation of the degU mutant in vivo is due to lysozyme sensitivity caused by the downregulation of pbpX and pgdA.…”
Section: Figmentioning
confidence: 76%
“…DegU is responsible for the expression of chemotaxis and (40,41,44,60). The data presented here suggest that the attenuation of the degU mutant in vivo is due to lysozyme sensitivity caused by the downregulation of pbpX and pgdA.…”
Section: Figmentioning
confidence: 76%
“…The DegU binding sites were identified in front of almost all regulated operons; however, only some of them were reported in the literature as parts of the DegU regulon. It is known that DegU in B. subtilis is an important regulator of many processes including chemotaxis, motility, extracellular secretion, quorum sensing and biofilm formation (Msadek et al, 1991;Murray et al, 2009;Gupta & Rao, 2014;Omer et al, 2015). It was reported that inactivation of DegU in B. amyloliquefaciens FZB42 led to impairing in efficient root colonization (Budiharjo et al, 2014).…”
Section: Gene Expression Profilingmentioning
confidence: 99%
“…ComA is an activator of many of the Rap proteins, thereby forming a complex regulatory network between the various QS pathways (18). Finally, RapG represses phosphorylated DegU (DegUϳP) (19), whose main functions are to promote the secretion of multiple enzymes and repress social motility (20). Recently, it was hypothesized that a plasmid-borne Rap (specifically, Rap carried by plasmid pLS20 [Rap pLS20 ]) may also interact directly with an Xre-type plasmidborne repressor (21).…”
mentioning
confidence: 99%